Neutrophil to lymphocyte ratio of patients who underwent bilateral versus unilateral unicompartmental knee arthroplasty - Nihat Demirhan Demirkiran (Medicine Science, 2020)
In recent years, the neutrophil-to-lymphocyte ratio (NLR) has emerged as a sensitive index of systemic inflammation. NLR predicts serious complications, such as pulmonary embolism or cardiovascular disease risk. Our study aims to compare the inflammation rate of bilateral simultaneous UKA versus unilateral UKA by using NLR. The medical records of 27 patients who underwent unicompartmental knee arthroplasty were reviewed retrospectively. The patients were divided into two groups. Group 1 consisted of 10 patients who underwent bilateral simultaneous UKA (bUKA), whereas group 2 consisted of 17 patients who underwent unilateral UKA (uUKA). Preoperative and postoperative 1st hour blood chemistries were performed and results were extracted from the electronic database. The neutrophil-to-lymphocyte ratio (NLR) was calculated from the absolute neutrophil and lymphocyte counts. The mean preoperative and postoperative NLR and the difference in NLR between the preoperative and postoperative 1st hour was calculated. The mean preoperative NLR was 2.13 (0.51-4.54), and the mean postoperative NLR was 7.06 (0.50-15.33) in the uUKA group. NLR was significantly higher in the postoperative 1st hour (p=0.001). In the evaluation of the bilateral group (bUKA), the mean NLR was calculated as 1.61 preoperatively and 9.38 postoperatively. Hence, there was a statistically significant difference (p=0.001). The mean difference in NLR was 7.77 in Group 1 and 4.92 in Group 2. Although the increase in NLR was higher in Group 1, no statistically significant difference was found (p=0.547). Our findings revealed similarly increased rates of NLR in the bilateral and unilateral UKA groups. Our study may suggest that bilateral simultaneous application of UKA is a safe procedure in terms of NLR-associated complications. [Med-Science 2020; 9(1.000): 227-30]